RISK MANAGEMENT IN SHARIA FINANCIAL TECHNOLOGY: Case Study of Peer to peer Lending Financing Model at PT Qazwa Mitra Hasanah - Ardiansyah, Jefri; Mustofa, Mustofa (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
This study aims to analyze risk management in Sharia-based Peer-to-Peer (P2P) lending, with a case study on PT Qazwa Mitra Hasanah. Sharia fintech has grown rapidly as an alternative financing source, particularly for MSMEs, which often face challenges in accessing traditional financial institutions. However, like conventional fintech, Sharia fintech also faces various risks from both the lender and borrower sides. Therefore, it is essential to understand how this business model manages risks in alignment with Sharia principles. This study adopts a qualitative research method with descriptive analysis. Data were gathered from literature sources, such as ebooks, company publications, government reports, previous research data, and official sources like Qazwa.id. The study also includes a risk analysis covering operational, financial, and legal aspects. Findings indicate that PT Qazwa, in its Sharia-based P2P lending model, implements comprehensive risk management, including risk identification, mitigation of credit risk, operational risk, Sharia compliance, and liquidity management. Risk identification is carried out through strict e-KYC verification to secure the identities of both lenders and borrowers. Credit risk mitigation involves Sharia-compliant credit scoring, portfolio diversification, and financial management education for MSMEs, thus reducing the risk of default.